Lung Cancer App (LuCApp) study protocol: a randomised controlled trial to evaluate a mobile supportive care app for patients with metastatic lung cancer. Issue 2 (15th February 2019) - Ciani, Oriana; Cucciniello, Maria; Petracca, Francesco; Apolone, Giovanni; Merlini, Giampaolo; Novello, Silvia; Pedrazzoli, Paolo; Zilembo, Nicoletta; Broglia, Chiara; Capelletto, Enrica; Garassino, Marina; Nicod, Elena; et al.
Abstract : Introduction: Mobile health technologies may enhance patient empowerment and data integration along the whole care continuum. However, these interventions pose relatively new regulatory, organisational and technological challenges that limit appropriate evaluation. Lung Cancer App (LuCApp) is a mobile application developed by researchers and clinicians to promote real-time monitoring and management of patients' symptoms. This protocol illustrates a clinical trial designed to evaluate the usability, effectiveness and cost-effectiveness of LuCApp versus standard of care. Methods and analysis: This is a 24-week two-arm non-blinded multicentre parallel randomised controlled trial. A total of 120 adult patients diagnosed with small or non-small cell lung cancer and eligible for pharmaceutical treatments will be allocated 1:1 to receiving either standard care or LuCApp in addition to standard care at three oncology sites in Northern Italy. During the treatment period, LuCApp allows daily monitoring and grading of a list of symptoms, which trigger alerts to the physicians in case predefined severity thresholds are met. Patients will complete a baseline assessment and a set of valid and reliable patient-reported outcome measures every 3±1 weeks, and up to 24 weeks. The primary outcome is the change in the score of the Trial Outcome Index in the Functional Assessment of Cancer Therapy (Lung) questionnaire from baseline to 12 weeks. Secondary outcomes are the Lung Cancer Subscale, the EuroQoL 5D-5L questionnaire, the Hospital Anxiety and Depression Scale, the Supportive Care Needs Survey Short Form, the app usability questionnaire and the Zarit Burden Interview for the main caregiver. Ethics and dissemination: The trial received ethical approval from the three clinical sites. Trial results will be disseminated through peer-reviewed publications and conference presentations. Conclusions: This trial makes a timely contribution to test a mobile application designed to improve the quality of life and delivery of care for patients with lung cancer. Trial registration number: NCT03512015; Pre-results.